Tribocorrosion behavior of additive manufactured Ti-6Al-4V biomedical alloy. (March 2018) - Buciumeanu, M.; Bagheri, A.; Shamsaei, N.; Thompson, S.M.; Silva, F.S.; Henriques, B.
Abstract: The tribocorrosion behavior of Ti-6Al-4V alloy as produced using different manufacturing/processing methods is experimentally investigated. Various Ti-6Al-4V specimens sourced from either casting, hot pressing (HP) or Laser Engineered Net Shaping (LENS) processes were analyzed via reciprocating sliding alumina contact tests under open circuit potential (OCP). Results indicate that the tribocorrosion behavior of Ti-6Al-4V parts depends on its manufacturing method. The additive manufactured, LENS Ti-6Al-4V samples showed better wear and corrosion resistance as compared to the Ti-6Al-4V samples produced by either casting or HP. This unique characteristic is attributed to the very high, localized cooling rates experienced during LENS resulting in the Ti-6Al-4V material having higher hardness and slight chemistry variation. Graphical abstract: Highlights: Tribocorrosion performance of Ti-6Al-4V alloy depends on how it is manufactured. The Ti-6Al-4V sample microstructures varied with manufacturing method employed. Process cooling rates impact final part corrosion resistance. The best wear and corrosion resistance was obtained in the case of LENS samples.